2012
DOI: 10.2519/jospt.2012.3787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Microwave Diathermy on Shoulder Pain and Function in Patients With Rotator Cuff Tendinopathy in Comparison to Subacromial Corticosteroid Injections: A Single-Blind Randomized Trial

Abstract: Shoulder pain is a common reason for consultation in general practice, with a 1-year prevalence ranging from 5% to 47% in the general population. 27Rotator cuff tendinopathy is the most common nontraumatic shoulder painful condition and affects about 20% of the population, with increasing prevalence over the course of aging. 28,33 The condition is characterized by a combination of pain and rotator muscle weakness, resulting in substantial limitations in overhead motor tasks and impairments in everyday activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 34 publications
0
32
0
5
Order By: Relevance
“…84 They found significant improvements in pain and function at 4, 12, and 24 weeks post-intervention in both groups and no significant between-group differences at any time point on any measure.…”
Section: Diathermymentioning
confidence: 90%
See 1 more Smart Citation
“…84 They found significant improvements in pain and function at 4, 12, and 24 weeks post-intervention in both groups and no significant between-group differences at any time point on any measure.…”
Section: Diathermymentioning
confidence: 90%
“…Both groups improved in function significantly at 12 weeks and 1 year post-intervention, but there were no significant between-group differences at any time point. 77 Rotator Cuff-Associated Disorders 84 Physical Therapy.…”
Section: Adhesive Capsulitismentioning
confidence: 99%
“…Other results indicated that there were no significant differences in QuickDASH scores or Constant-Murley Score for the participants when comparing diathermy with corticosteroids in the treatment of rotator-cuff tendinopathy. 3 The summary of these results would indicate that diathermy is significantly better at reducing pain than ultrasound treatments 1,2 and equally as effective at reducing pain levels as a corticosteroid injection. 3 Although the studies show statistically significant results, there are differences between the studies that must be noted.…”
Section: Rabini Et Almentioning
confidence: 99%
“…In the studies reviewed for the CAT, diathermy treatments were compared with ultrasound treatment, 1,2 exercise protocols, 2 and corticosteroid injection treatment. 3 Both studies by Giombini et al 1,2 compared the effectiveness of diathermy as a treatment for tendinopathy with ultrasound. Those studies revealed that diathermy reduced the participants' pain levels significantly more than the ultrasound treatment.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation